Health systems in low- and middle-income countries : an economic and policy perspective - Smith, Richard, 1968 July 15-; Hanson, Kara. (Oxford : Oxford University Press, 2012)
Outlines the key aspects & issues concerning health systems of low- & middle-income countries, recognising the current global context within which these systems operate & the dynamics of this context. It brings together a set of renowned authors to tackle the issues that face population health & health care in the twenty-first century.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Medical economics -- Developing countries; Medical policy -- Developing countries